Regenerative Marine Tourism Strategy in The Ecosystem of Momparang Archipelago, East Belitung: Strategi Wisata Bahari Regeneratif Di Ekosistem Kepulauan Momparang Belitung Timur - Dani Fauzi; Randi Syafutra; Erlingga Agustina (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
This research formulates a regenerative marine tourism strategy for the Momparang Archipelago, East Belitung, using the seven regenerative tourism principles. Key results show that conservation initiatives, such as coral reef restoration and environmental education, have engaged local fishermen and tourism operators in sustainability efforts. However, challenges in waste management and governance remain, requiring stronger frameworks to ensure long-term success. The study employs a qualitative approach with Logical Framework Analysis (LFA) to systematically identify goals, objectives, activities, and expected outcomes. Leveraging the region's unique cultural and ecological assets, such as shipwreck sites and Bugis Buton heritage, has been shown to enhance the destination’s appeal. Community involvement in conservation and waste management is critical to achieving a sustainable tourism model. Key recommendations include the formation of a multi-stakeholder regenerative tourism advisory board and continuous public education on sustainable practices. Future research should explore the broader application of regenerative tourism principles in other coastal areas, focusing on collaboration between government, local communities, and the private sector. Additionally, innovative waste management strategies that involve active tourist participation should be further investigated to enhance both environmental sustainability and visitor experience. This research offers a foundation for transforming the Momparang Archipelago into a model for sustainable regenerative tourism.